(untitled) (International Journal of Psychosocial Rehabilitation, 2020)
The article is devoted to the lexical-semantic, etymological and cognitive analysis of the specifics of the translation of some socio-political terms of the Chinese language, the genesis of the development of some terms related to the foreign policy of ancient China. The analysis of some socio-political terms according to their etymological characteristics, the formation and development of terms in the era of the establishment of diplomacy in Ancient China showed a growing trend of interaction between the national and international target audience of China. Depending on the political origin, historical impacts in the domestic and foreign policy of China, socio-political terms include definitions relating to nationally significant events of socio-political life, as well as other aspects related to the economy and culture. In this regard, translators should pay attention to the fact that when translating general cultural words, it is more accurate to take into account the cultural traditions of China and historical background